Analysis of gene expression and ultrastructure of stifle menisci from juvenile and adult pigs - Kreinest, Michael; Reisig, Gregor; Fickert, Stefan; Brade, Joachim; Schwarz, Markus (Comparative medicine, 2016)
The origin of the age-associated degenerative processes in meniscal tissue is poorly understood and may be related to an imbalance of anabolic and catabolic metabolism. The aim of the current study was to compare medial menisci isolated from juvenile pigs and degenerated medial menisci from adult pigs in terms of gene expression profile and ultrastructure. Medial menisci were isolated from the knee joints of juvenile and adult pigs (n = 8 for each group). Degeneration was determined histologically according to a scoring system. In addition, the gene expression profiles of 14 genes encoding extracellular matrix proteins, catabolic matrix metalloproteinases and mediators of inflammation were analyzed. Changes in the ultrastructure of the collagen network of the meniscal tissue were analyzed by using transmission electron microscopy. The histologic analysis of menisci showed significantly higher grade of degeneration in tissue isolated from adult porcine knee joints compared with menisci isolated from juvenile knee joints. In particular, destruction of the collagen network was greater in adult menisci than in juvenile menisci. Degenerated menisci showed significantly decreased gene expression of COL1A1 and increased expression of MMP2, MMP13, and IL8. The menisci from adult porcine knee joints can serve as a model for meniscal degeneration. Degenerative changes were manifested as differences in histopathology, gene expression and ultrastructure of collagen network.